Enhanced photoelectrochemical performance of quantum dot-sensitized solar cell using Cu2+ co-doped CdS and CdSe nanoscrystals - Thi Tran Anh Tuan; Ha Thanh Tung; Truong Thi Ngoc Chinh; Phan Thanh Hung; Huu Phuc Dang (Royal Society Open Science, 2024)
Today, nanoscrystals are researched and developed very quickly because of their advantages in many areas of life. One of the potential applications is quantum dot-sensitized solar cells. This is a green, clean, environmentally friendly cell, and has been studied by scientists since 2000. In this study, we fabricated photoanodes with Cu2+ ions co-doped into cadmium sulfide (CdS) and cadmium selenide (CdSe) nanoscrystals by successive ionic layer adsorption and reaction, and chemical bath deposition methods to improve absorption spectral intensity of films. The results showed that the absorption intensity increased by eight times compared with our previous results on Cu2+ ions doped with CdSe nanoscrystals. The CdS:Cu2+ film is optimized at 2% doping, the efficiency is 4.6819%, and the current density is 27.3501 mA.cm−2, which is higher when compared with the Cu2+ ion only doped into the CdSe quantum dot (19.915 mA.cm−2). In addition, the composition of the photoanode was determined by surface and cross-sectional field-emission scanning electron microscope images, and the structure of the film was determined by X-ray diffraction, energy-dispersive X-ray spectroscopy mapping and X-ray photoelectron spectroscopy. Finally, the film's optical properties were studied by ultraviolet-visible spectroscopy, photoluminescence spectroscopy and electrochemical properties by electrochemical impedance spectroscopy. The results obtained have been discussed and presented in great detail.